Acetate Oxidation Coupled to Fe(III) Reduction in Hyperthermophilic Microorganisms - Tor, Jason M. (American Society for Microbiology, 2001)
No hyperthermophilic microorganisms have previously been shown to anaerobically oxidize acetate, the key extracellular intermediate in the anaerobic oxidation of organic matter. Here we report that two hyperthermophiles, Ferroglobus placidus and “Geoglobus ahangari,” grow at 85°C by oxidizing acetate to carbon dioxide, with Fe(III) serving as the electron acceptor. These results demonstrate that acetate could potentially be metabolized within the hot microbial ecosystems in which hyperthermophiles predominate, rather than diffusing to cooler environments prior to degradation as has been previously proposed.